The Oxford handbook of industrial hubs and economic development - Oqubay, Arkebe; Lin, Justin Yifu, 1952- (Oxford : Oxford University Press, 2020)
Industrialization supported by industrial hubs has been widely associated with structural transformation and catch-up. But while the direct economic benefits of industrial hubs are significant, their value lies first and foremost in their contribution as incubators of industrialization, production and technological capability, and innovation. This handbook adopts an interdisciplinary approach to examine the conceptual underpinnings, review empirical evidence of regions and economies, and extract pertinent lessons for policy reasearchers and practitioners on the key drivers of success and failure for industrial hubs.
Industrial Hubs and Economic Development: An Introduction / Arkebe Oqubay, Justin Yifu Lin -- Industrial Districts in Europe: Lessons for Industrial Hubs and Industrialization / Gioacchino Garofoli -- A Global History of the Political Economy of Special Economic Zones / Patrick Neveling -- Cluster Dynamics and Regional Networks: New Argonauts, Silicon Valley and Route 128 / AnnaLee Saxenian -- Agglomeration of European Industries / Michael A. Landesmann, Joris M. Schröder -- The Global Experience in Special Economic Zones: A History and Review / Thomas Farole -- Leapfrogging Through Smart Manufacturing: The Role of Hubs in Industry 4.0 / Padmashree Gehl Sampath -- The Economics of Agglomeration / Célestin Monga -- An Urban Planning Perspective of Industrial Hubs and Economic Development / Fantu Cheru, Aklilu Fikresilassie -- Special Economic Zones and export-led growth: An Industrial Policy Imperative / Ludovico Alcorta, Taffere Tesfachew -- A Flowchart Approach to Industrial Hubs / Akifumi Kuchiki -- Industrial Hubs and Economic Development: A Literature Review / Arkebe Oqubay -- Industrial Hubs and the Industrial Labor Force in Africa and Asia / Carlos Oya, Florian Schaefer -- Gender, Industrialization, and Industrial Hubs / Fiona Tregenna, Özge İzdeş -- Women, Working Conditions and Industrial Hubs / Arianna Rossi -- Special Economic Zones in Latecomer Countries: Time to Bring Environmental Sustainability to the Fore / Giovanni Valensisi -- Greening of Industrial Hubs: A 21st Century Development Strategy / John A. Mathews -- Greening Structural Transformation: What Role for Industrial Hubs? / Tilman Altenburg, Kasper Vrolijk -- Towards a New Generation of Special Economic Zones: Sustainable and Competitive / James X. Zhan, Bruno Casella, Richard Bolwijn -- Industrial Hubs as development incubators: Asian Pioneers / Arkebe Oqubay -- Explaining the Reform and Special Economic Z
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on July 31, 2020).
Keywords: Industrial clusters -- Economic aspects; Industrial sociology; Industrialization; Economic development